'Ending AIDS' in the age of biopharmaceuticals : the individual, the state and the politics of prevention - Sandset, Tony, 1982- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book considers the change in rhetoric surrounding the treatment of AIDS from one of crisis to that of 'ending AIDS'. Exploring what it means to 'end AIDS' and how responsibility is framed in this new discourse, the author considers the tensions generated between the individual and the state in terms of notions such as risk, responsibility and prevention. Based on analyses public health promotions in the UK and the U.S., HIV prevention science and engaging with the work of Foucault, this volume argues that the discourse of 'ending AIDS' implies a tension-filled space in which global principles and values may clash with localised needs, values and concerns; in which evidence-based policies strive for hegemony over local, tacit and communal regimes of knowledge; and in which desires compete with national and international ideas about what is best for the individual in the name of 'ending AIDS' writ large. As such, it will appeal to scholars of sociology and media studies with interests in the sociology of medicine and health, medical communication and health policy"--
A Short History towards the End of AIDS -- Viral load maps : The entanglements between the individual, the community, and space -- Molecular HIV surveillance : issues of consent, ethics, and molecular truth telling -- PrEP : the public life of an intimate drug -- 'HIV both starts and stops with me' : health promotions, neoliberalism and responsibility -- 'The category is : Suppress! Disclose! Survive!', 'Positive living' in health promotions for people living with HIV in the era of the end of AIDS -- Conclusion : a tentative end to AIDS?
OCLC-licensed vendor bibliographic record.
Keywords: AIDS (Disease) -- Treatment; AIDS (Disease) -- Prevention; Medical policy; Health promotion; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General